(untitled) (Промышленный Транспорт Казахстан, 2025)
The purpose of this article is to summarise the major changes affecting transport systems in the UK over the last 100 years. The first section identifies significant points of change in the main transport modes. The second section addresses the principal factors accounting for these changes. The third section examines the consequences for the economy, social inequality and the environment. The article also refers to the overarching trends and issues for consideration. From the historical analysis five issues were identified as relevant to the future of transport in the UK. Interactivity: while transport analysis and policy is often directed towards single modes (e.g. road, rail), it is clear that developments in some modes have been closely connected with those in others. Most journeys in the past were multi-modal. Mobility revolution: evidence points to a transformation in personal mobility in the later twentieth century, driven by consumer demand. Transformation has occurred in scale and scope in automobility, air travel and, more recently, rail travel. Overload: one of the results of the surge in the circulation of people and goods has been overloaded transport systems: congested roads, crowded trains and airports. Sustainability: since the oil crisis of 1973 the sustainability of transport has been a major issue, encompassing renewable resources, carbon emissions and pollution. Government has worked towards greater sustainability but it remains a major challenge. Alternatives: transport systems have been relatively stable over the last century, qualifying the idea of an imminent breakthrough to a new phase of transport. History suggests that change is as much a matter of recycling the old as introducing the new. The past thus remains an important resource for transport alternatives in the future.